Conservation and enhancement of natural resources - Vosti, Stephen A.; Scherr, Sara J. (International Food Policy Research Institute, 1994)
Meeting food and livelihood security needs in developing countries will require the conservation and enhancement of natural resources that contribute to agricultural production. Chief among the resources to be sustainably managed are soils and forests. Once forests fall, what land-use patterns emerge, and what are the consequences of the new land-use patterns for food security and the environment? Finally, what can be done by policymakers to simultaneously reduce poverty and deforestation rates?